The influence of the environment on the volume growth, stem form and disease tolerance of Eucalyptus grandis clones in the summer rainfall areas of South Africa - Pierce, Brian Thomas (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2000.